Phase transitions in compressed metil silica with the participation of water and methanol - Turov, V.V.; Krupska, T.V.; Kartel, M.T. (Physics and Chemistry of Solid State, 2025)
Methanol, water, and their mixtures in the interparticle gaps of wetting-drying methyl silica AM-1 were studied using low-temperature 1H NMR spectroscopy. The bulk density of the samples in the wet state was 200-300 mg/cm3. It is shown that both on dry and on wet samples of methyl silica AM-1, methanol melts up to 280 K, which is 100 degrees higher than the bulk melting temperature. Water is present in the form of nanoscale clusters of strongly and weakly associated water on wet hydrocompacted samples of methylsilica. It is assumed that weakly associated water is a nanoscale analogue of supercritical water. It mixes well with weakly polar chloroform or polar methanol. In the latter case, a concentrated solution of unassociated molecules of water and methanol is formed in the interparticle gaps of methyl silica AM-1. As the temperature decreases, both strongly and weakly associated water freeze and cease to be registered in liquid NMR spectra.